Broadband Circular Polarizer Based on Multilayer Gradual Frequency Selective Surfaces - Wei Zhang; Jian-ying Li; Ling Wang (International Journal of Antennas and Propagation)
This paper presents a broadband circular polarizer based on multilayer gradual frequency selective surfaces. The unit cell includes two identical circles and a bar, whose dimensions decrease layer by layer with a reduction factor. This design can provide a good phase difference that is close to 90°. The bandwidth of the polarizer reaches 66.7%, from 7.9 to 15.8 GHz, which can convert the incident linear polarization waves into circular polarization waves. A sample polarizer is fabricated and measured. The results show that the operation frequency ranges from 7.75 to 15.2 GHz, coinciding with the simulation. Meanwhile, the working frequency band covers the range of 8.2–14.5 GHz when the incident angle increases to 25°.